Anti-ulcer Activity of Various Polar & Non Polar Extracts of Leaves of Alstonia scholaris Linn. in Different Models of Ulceration - Yogendra Singh Shakya*, Dr. Gajendra Singh Rathor, Dr.Pushpendra Singh Naruka (International Journal of Advanced Science and Technology, 2022)
AIM- The present aim of the study is to study Anti-ulcer Activity of Various Polar & Non Polar Extracts of Leaves of Alstonia scholaris Linn. in Different Models of Ulceration. MATERIAL & METHODS- Drug was subjected to extraction with chloroform, ethyl acetate in soxhlet apparatus, the extraction was completed in 17-18 cycles. The extract was dried & stored in dark place. Drug was subjected to extraction with ethanol in soxhlet apparatus, the extraction was completed in 25 cycles. The extract was dried & stored in dark place. The Drug was subjected to extraction with water by Hot Water Extraction. Acute oral toxicity test was carried out according to the OECD guideline No. 423. The animals were treated with test extracts or standard or control according to the various groups had been designed. 1 hour later 80% alcohol was administered p.o. to each animal. Animals were sacrificed 1 hour after alcohol administration, stomach were isolated, cut and opened along the greater curvature and pinned on a soft board. Ulcer index parameters were studied according to standard protocol of Kulkarni SK. In pylorus ligation method, albino rats were fasted in individual cages for 24 hours. Test extracts or standard drug or control vehicle was administered 30 minutes prior to pyloric ligation. RESULTS- The ethanolic extract of leaves caused a reduction in the severity of these lesions induced by ethanol which was evident by a moderately significant (p<0.01) reduction in the ulcer index and an increase in the percentage protection of ulcers when compared with the control group. The results indicated that ethanolic extract at dose levels of 200 mg/kg and 400 mg/kg significantly decreased the ulcer index (p><0.001) which was also evidenced by significant increase in percentage ulcer protection at both the dose levels. CONCLUSION-In our study, ethanolic extract of leaves also showed a significant percentage protection against ulcer formation in pylorus ligation model, ethanol induced model in rat at the dose of 200 and 400 mg/kg. >